2018
DOI: 10.1016/j.pharep.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiglycating effect and in vivo neuroprotective activity of Trigonelline in d -galactose induced cognitive impairment

Abstract: Present study highlights the neuroprotective role of TRG against d-gal induced amnesia due to the antioxidant, antiglycative and anticholinesterase properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Trigonelline, an alkaloid identified at m/z 138.0555 ((M + H) + ), inhibited AChE with an IC 50 value of 233 µM while 1.27 µM was recorded for galantamine [23]. Trigonelline was administered to d-galactose induced cognitive impaired mice and a significant decline in AChE level along with reduced oxidative stress and advanced glycation end products levels were observed [24]. It is important to highlight that the higher inhibitory action of the methanol extract of P. africanum stem bark on AChE and BChE might be related to the synergistic action of multiple phytochemicals rather than one single molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Trigonelline, an alkaloid identified at m/z 138.0555 ((M + H) + ), inhibited AChE with an IC 50 value of 233 µM while 1.27 µM was recorded for galantamine [23]. Trigonelline was administered to d-galactose induced cognitive impaired mice and a significant decline in AChE level along with reduced oxidative stress and advanced glycation end products levels were observed [24]. It is important to highlight that the higher inhibitory action of the methanol extract of P. africanum stem bark on AChE and BChE might be related to the synergistic action of multiple phytochemicals rather than one single molecule.…”
Section: Resultsmentioning
confidence: 99%
“…In the meantime, there are experiments have shown that injecting Aβ1-40 directly into the hippocampus can induce the changes in the main pathological characteristics and cognitive dysfunction in Alzheimer’s disease model rats [ 20 , 21 ]. Despite there were studies showed that intraperitoneal injection of D-gal alone [ 22 ] or injection of Aβ1-40 alone [ 20 ] will results in changes of Aβ levels in the brain and caused cognitive dysfunction. But there is no research directly compared the combination of these two modeling methods with use of them individually.…”
Section: Discussionmentioning
confidence: 99%
“…D-Galactose induced cognitive impairment: D-galactose (D-gal) is a natural reducing sugar that is mainly derived from lactose in the milk. Studies have showed that an excess of D-gal leads to abnormal metabolism due to the reduction in Na + , K + , ATPase activity, excessive oxidative stress due to enhanced lipid peroxidation and downregulation of the superoxide dismutase activity [66] , neuronal damage due to advanced glycation [62] and neuroinflammation [63] , [64] , [65] and increased senile plaques formation [66] , tau phosphorylation [68] leading to cognitive impairment in rodents [67] . It is known to cause alteration in hippocampal gene expressions [64] .…”
Section: Methods Detailsmentioning
confidence: 99%
“… d-gal (150 mg/kg) for 6 weeks. [62] , [63] , [64] , [65] , [66] , [67] , [68] 20 Dizocilpine (MK-801) AD Male Wistar rats aged 8-10 weeks Male C57L/B6 mice aged 7-9 weeks Cognitive deficits, motor disturbances 0.15mg/kg,i.p., [69 , 70] 21. Diazepam Male Swiss albino mice -young (3-4 months) and aged (12-15 months) Cognitive deficits 1mg/kg., i.p [15 , 75] …”
Section: Introductionmentioning
confidence: 99%